การพัฒนาบทเรียนอิเล็กทรอนิกส์สำหรับระบบปฏิบัติการแอนดรอยด์ เรื่อง จำนวนและการดำเนินการ วิชาคณิตศาสตร์ สำหรับนักเรียนชั้นประถมศึกษาปีที่ 3 - Dorkkhamklang, Chorpaka; Manosuttirit , Artnarong; Wannaprapha, Thanawat (Journal of Graduate School Sakon Nakhon Rajabhat University, 2022)
The purposes of this research were 1) to develop electronics lessons for android on numbers and operations of Mathematics subject for Prathomsuksa 3 students to meet the efficiency based on the E1/E2 formula with the 80/ 80 criteria, and 2) to examine the learning achieving scores after learning through the developed lessons, and 3) to explore the students’ satisfaction with the use of the developed lessons. The sample consisted of 30 students from a class of Prathomsuksa 3 at Bannoenmok School in the 2020 academic year. The research instruments were 1) the electronics lessons for android on numbers and operations of Mathematics subject for Prathomsuksa 3 students, 2) a learning achievement test, 3) a questionnaire on students’ satisfaction with the use of the developed lessons, and 4) exercises for each lesson. The statistics for data analysis were percentage, mean, standard deviation, and the efficiency test with the efficiency criteria E1/E2. The results revealed that 1) the electronics lessons for android on numbers and operations for Prathomsuksa 3 students with the defined efficiency of 80.06/ 81.76, and the learning achievement test scores after the intervention were higher than those before the intervention with 11.54 percent, and the students’ satisfaction towards the developed lessons was overall at a high level.